The maiden and the dragon - Marco Simón, Francisco (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
In the ancient city of Lanuvium (Latium), young women and snakes played a key role in the cult of the goddess Juno Sospita, as both Roman monetary iconography and literary testimonies testify. The purpose of these lines is to address, together with the analysis of these rituals with their parallels in the classical world, their resemantization by late Christian authors (in a context characteristic of the demonization of ancient cults) and their use, in a more properly mythical horizon, in later hagiographic contexts such as that of St. George.
Keywords: Juno Sospita; Vestal Virgins; cultural appropriation; Christian hagiography; St. George